Therapeutic Targeting of Eosinophil Adhesion and Accumulation in Allergic Conjunctivitis - Baiula, Monica; Bedini, Andrea; Carbonari, Gioia; Dattoli, Samantha D.; Spampinato, Santi (Frontiers in Pharmacology, 2012)
Considerable evidence indicates that eosinophils are important effectors of ocular allergy. Increased worldwide prevalence of allergic eye pathologies has stimulated the identification of novel drug targets, including eosinophils and adhesion molecules. Accumulation of eosinophils in the eye is a key event in the onset and maintenance of allergic inflammation and is mediated by different adhesion molecules. Antihistamines with multiple mechanisms of action can be effective during the early and late phases of allergic conjunctivitis by blocking the interaction between β1 integrins and vascular cell adhesion molecule (VCAM)-1. Small molecule antagonists that target key elements in the process of eosinophil recruitment have been identified and reinforce the validity of α4β1 integrin as a therapeutic target. Glucocorticoids are among the most effective drugs for ocular allergy, but their use is limited by adverse effects. Novel dissociated glucocorticoids can prevent eosinophil accumulation and induce apoptosis of eosinophils, making them promising candidates for ophthalmic drugs. This article reviews recent understanding of the role of adhesion molecules in eosinophil recruitment in the inflamed conjunctiva along with effective treatments for allergic conjunctivitis.